The Digital Madrasah as an Idea of IT-Based Islamic Education - Sedya Santosa; Muhammad Fahmi Jazuli (Nazhruna: Jurnal Pendidikan Islam, 2022)
In this article, the author will review the opportunities for madrasah as Islamic educational institutions in facing modernization, as well as what learning methods are appropriate to use in learning. The term "digital madrasa" can become a bridge for a madrasah to be ready to face the era of globalization. This study uses a library research method, namely research conducted using library research, which can be in the form of books, notes, or reports of previous research results. The results of the study showed that a digital madrasah is a madrasah that organizes education management using digital applications. The application of ICT is not only in the realm of learning but also in the realm of madrasah governance, evaluation, and educational environments that are aware of the use of technology. Learning to use e-learning has become a must if you want to create a digital-based school. Synchronous approach, asynchronous blended learning is an approach that can be chosen in digital learning.